PERSEPSI MAHASISWA DESAIN INTERIOR TERHADAP ESTETIKA LINGKUNGAN TEPI SUNGAI DI YOGYAKARTA - Artbanu Wishnu Aji (Institut Seni Indonesia Yogyakarta, 2017)
Riverside development in Indonesia will involve many elements of the society. Goverment policies on riverside development will be affected by social dynamics and contemporary issues in the society. One of these social elements is interior designer students who join the force to improve river condition in Yogyakarta. As young designers who can directly affected environments by their design, their design’s vision needs to be identified in order to find their preferences toward riverside environments. This research aimed to find interior designer students’ aesthetics preference and their vision of the future riverside environment. Data were gathered using questioanere and administered to 101 students. 4 riverside scenic view were chosen as aesthetic stimulus to the students to be rated with semantic deferential scale. The result from SPSS 18 showed that students’ preference is toward kewek river environment and their future preference is toward tradisional design rather than the modern.